THE USE OF VOCABULARY LEARNING STRATEGY BY JUNIOR HIGH SCHOOL STUDENTS (RETAIN, 2017)
THE USE OF VOCABULARY LEARNING STRATEGY BY JUNIOR HIGH SCHOOL STUDENTS Arpinda Syifaa Awalin English Department Faculty, Faculty of Language and Arts, State University arfindasyifa@gmail.com Abstrak Strategi pembelajaran vocabulary digunakan siswa yang memiliki penegtahuan vocabulary dengan jumlah banyak dan sedikit untuk membantu mereaka dalam belajar vocabulary. Kita ketahui bahwa vocabulary adalah salah satu aspek yang mempengaruhi dalam belajar bahasa. Inggris. Oleh karena itu, penelitian ini dilakukan untuk mengetahui tentang strategi pembelajaran vocabulry yang digunakan oleh siswa SMP yang memiliki banyak atau sedikt pengetahuan mereka mengenai vocabulary dan alasan mereka mengapa mereka menggunakan strategi pembalajaran vocabulary tersebut. Questionare dan wawancara adalah intrument untuk mendapatkan data. Hasil dari penitilain ini menunjukkan bahwa diantara siswa yang memiliki banyak atau sedikt pengetahuan mereka mengenai vocabulary menggunakan startegi yang berbeda sesuai dengan gaya dan kebiasan mereka. Menurut ketiga macam stratehi pembelajaran vocabulary (i.e discovery, social and consolidate strategy), setiap siswa mengunakan sub strategi yang dapat membetu mereka dalam belajar vocabulary. Disatu sisi, penggunaan strategi ini membuat siswa mudah untuk belajar dan mengingat vocabulary. Kata kunci: Strategi Pembelajaran Vocabulary, siswa yang memiliki pengetahuan banyak dan sedikit tentang vocabulary, Alasan Abstract Vocabulary learning strategy is used by students who have large and small vocabulary size to help them in learning vocabulary. Since we know vocabulary is one aspect which influences in learning English. Therefore, this study is conducted to know about the vocabulary learning strategy which used by junior high school students who have large and small vocabulary size and the reason why students used vocabulary learning strategy. The data were collected from questionnaires and interview. The results of study shown among students who have large and small vocabulary size used the different vocabulary learning strategy based on their passion. Based on three types of vocabulary learning strategy (i.e discovery, social and consolidate strategy), each of students used the sub strategy which help them in learning vocabulary. On the other hand, using this strategy makes students to learn and memorize the new vocabulary easily. Keywords: Keywords: Vocabulary Learning Strategy. Students with Large Vocabulary Size, Students with Small Vocabulary Size, Reason